Critical Discourse Analysis of Class and Power in A Cup of Tea and The Necklace: An Intertextual Approach - Hitakumala, Nur Azizah (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study analyzes the representation of class and power in two short stories, A Cup of Tea and The Necklace, using the theory of Critical Discourse Analysis by Norman Fairclough and the intertextuality approach by Julia Kristeva. The main objective of this study is to reveal how the concepts of class and power are represented through the main characters in both stories and how the intertextual relationship between the two reflects broader social dynamics. This study uses a qualitative descriptive method with in-depth reading techniques to collect relevant quotations. The results show that there are differences in the representation of class and power between the two main characters. Rosemary in A Cup of Tea represents the hegemony of the upper class through her wealth and social control, while Mathilde in The Necklace reflects the ambition and social pressure experienced by the lower middle class in meeting social demands influenced by capitalism. In addition, the intertextual analysis reveals that both stories are related in criticizing the social pressures that arise from capitalism, especially those experienced by women. Both highlight how social expectations shape the desires and behavior of the main characters and depict the impact of the class system on individuals, especially women, in a patriarchal society.